2013
DOI: 10.1016/j.jval.2013.08.558
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Caregivers’ Preferences for Bone Metastases (BM) Treatments in the United States

Abstract: tiveness analyses were compared with methods specified by NICE as the reference case in its 2004 and 2008 Methods Guides. The review focused on guidance published before June 2013 for medicines treating metastatic breast cancer, metastatic colorectal cancer, metastatic hormone-refractory prostate cancer and metastatic non-smallcell lung cancer. Nineteen technology appraisals published between March 2002 and August 2012 met the inclusion criteria. Results: Common themes or variations that exist between utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…14,15 In a study of physicians, patients, caregivers, and nurses in the USA, out-of-pocket cost to patients, time to first SRE, and risk of renal impairment were rated as the most important BTA attributes by each group. [30][31][32] These studies confirm that treatments that delay SREs and worsening of pain with a low risk of renal impairment are desirable in the opinions of both patients and physicians across Europe and the USA.…”
Section: International Journal Of Hematology and Oncologysupporting
confidence: 52%
“…14,15 In a study of physicians, patients, caregivers, and nurses in the USA, out-of-pocket cost to patients, time to first SRE, and risk of renal impairment were rated as the most important BTA attributes by each group. [30][31][32] These studies confirm that treatments that delay SREs and worsening of pain with a low risk of renal impairment are desirable in the opinions of both patients and physicians across Europe and the USA.…”
Section: International Journal Of Hematology and Oncologysupporting
confidence: 52%
“…as the most important attributes when choosing pharmacologic therapy for the prevention of SREs in patients with bone metastases due to solid tumors. Given that out-of-pocket costs are the most important attribute in this analysis, it seems that physicians understand that such costs, which vary in the United States by health plan and coverage, are an important factor for patients, and indeed, studies have confirmed that this is of relatively equal importance for both physicians and patients [27]. These observations underscore the importance of increasing awareness of health plan coverage and patient support programs to enable caregivers to present a more comprehensive view of available treatment options for bone metastases, facilitating a joint treatment decision between physicians and patients.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 Given the wide variation in adherence to recommended treatment guidelines due to patient or provider preference, patient comorbidities, or contraindications, assessment of real-world BTA treatment patterns in patients with BM is essential. [26][27][28] Previous realworld studies of BTA treatment patterns in the US have reported that 47.0% of Medicare and 43.2% of commercially insured patients with BM across cancer types were administered BTAs. 24 The proportion of BTA-treated patients with breast cancer in the US was 66.6% to 69.0%, 24,29 which is lower than that for Europe, where 88% of patients with breast cancer received BTAs after BM diagnoses; 28 delays in BTA administration were often associated with the physician's decision.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of real-world BTA treatment patterns in patients with BM in the US is limited 24,25 . Given the wide variation in adherence to recommended treatment guidelines due to patient or provider preference, patient comorbidities, or contraindications, assessment of real-world BTA treatment patterns in patients with BM is essential 26–28 . Previous real-world studies of BTA treatment patterns in the US have reported that 47.0% of Medicare and 43.2% of commercially insured patients with BM across cancer types were administered BTAs 24 .…”
Section: Discussionmentioning
confidence: 99%